Study on 40 cases of rickettsia - Miah, MT; Rahman, S; Sarker, CN; Khan, GK; Barman, TK (Mymensingh Medical Journal, 2007)
The abstract of this article is available on the PubMed websiteMymensingh Med J. 2007 Jan;16(1):85-8